Dark Saturday [large type] : a novel - French, Nicci (A Frieda Klein mystery, 2017)
French's suspenseful but clumsily plotted sixth Frieda Klein thriller (after 2015's Friday on My Mind) finds the London psychotherapist under pressure from shadowy power brokers to stick her nose into one of the country's most notorious crimes. They ostensibly just want her expert opinion on whether Hannah Docherty, convicted as a teen 13 years earlier for the slaughter of her family, seems likely to challenge the verdict now that irregularities have been discovered in another, related murder probe. Appalled by the condition in which she discovers a clearly brutalized Hannah at the notorious Chelsworth forensic facility, Frieda does a bit of digging-and starts to suspect the young woman was framed. That suspicion becomes a virtual certainty when a key source is killed.